Gênero, raça e ação afirmativa no Mato Grosso do Sul: uma experiência brasileira - Sena, Ana Lúcia da Silva (2011)
Since the 90s some electoral reforms in countries from Latino America have produced results which a deeper analysis is indispensable for understanding women's access to positions in various spheres of public power. In this academic work this issue is going to be discussed. This study aims to point out new empirical evidence to the debate about participation, inclusion and representation of women in the political process in Mato Grosso do Sul, Brazil. For this purpose, a deep analysis of the election results within the state will be necessary. In this work, a discussion regarding the historical and political processes found in the hegemonic and oligarchic forces, in the power until nowadays, is raised with the aim of debating the a social inversion in which such processes had overcame the categories of gender and race. A racial dimension is needed to understand the ethnic-racial diversity existing in society. Therefore, an important component to consider in this discussion is the process of racial hierarchy associated with whiteness that show the perverse effects of racism in Brazil. Although, women should have a more representative role in politics, there are still a small number of them in the public power, therefore fostering a debate to understand its reasons. In the conclusion, other factors that impede the success of women in politics are presented. In this dissertation, the lack of commitment from the politicians that fostered the inequalities of gender and race is also discussed, therefore showing unfavorable results to not the women but also all Brazilian society